Foreign Language Learning via Online Modular Instruction and Related Variables: A Sequential Explanatory Study - Jeremie Monter Maleon; Robert Carl Jermanie Garcia; Blossom Buenaventura Gasper (Journal of Foreign Language Teaching and Learning, 2022)
This study describes the relationship between the respondents’ foreign language learning proficiency and the following variables: Respondent- related Factors, Teacher Factors, School Factors, and Home Factors. A survey questionnaire based on the Theory of Performance (ToP) by Elger (2007) was used to gather data about the factors. Meanwhile, the grades in a foreign language class of 25 college students were collected for the correlation. The quantitative data were processed through the SPSS software using the Pearson Product- Moment Correlation Coefficient formula, while the NVivo software was run to process the qualitative responses that served as a follow-up to the correlation results. Findings revealed that none of the four factors significantly correlated with the respondents’ FL grades, but one item under School Factors was found to have a moderate positive correlation with the FL grades. Furthermore, the respondents’ attitudes towards online learning, fathers’ educational background, and teacher factors resulted in a weak positive correlation. The themes from the qualitative data also supported the correlation findings.